Perancangan Sistem Prediksi Pembelian Stok Masker dengan Metode Fuzzy Mamdani (Studi Kasus: Ud Masker Murah Jogja) - Asman, Muhammad; Guatama, Deden Hardan; Wijaya, Dhina Puspasari; Pramuntadi, Andri (Jurnal Teknik Industri Terintegrasi (JUTIN), 2023)
This research aims to design a fuzzy Mamdani-based prediction system to assist in stock management decision-making for masks at UD MASKER MURAH JOGJA. The system will provide recommendations for mask brands with the highest sales and revenue. The fuzzy Mamdani method is considered effective in addressing subjectivity and providing highly precise mask stock predictions. This research will also consider profit variables as additional attributes to enhance prediction accuracy. The prediction system will help UD MASKER MURAH JOGJA make informed decisions in mask stock management, with the goal of maximizing profits and overcoming subjectivity. The results obtained from the fuzzy Mamdani method will reduce subjectivity, and the developed web system will function as intended.